The Influence of Brand Image, Brand Trust, and Brand Satisfaction on Brand Loyalty of Eiger Adventure - Nugrahanta, Septi; Ariani, Dorothea Wahyu (East Asian Journal of Multidisciplinary Research, 2024)
The purpose of this research is to examine how the Yogyakarta-based Eiger Adventure brand's image, trust, and satisfaction affect customer loyalty. Conducted by distributing questionnaires to 100 customers, the research used a quantitative approach to examine causal relationships, employing descriptive analysis, inferential analysis, and t-tests. Brand loyalty is unaffected by brand image, according to the findings. However, brand trust positively and significantly influences brand loyalty, showing that higher trust leads to greater loyalty to Eiger Adventure. Additionally, brand satisfaction also positively and significantly impacts brand loyalty, meaning customer satisfaction with Eiger Adventure's products and services enhances their loyalty. Although brand image did not have a substantial influence on consumer loyalty, the research does highlight the significance of trust and happiness with the brand.